2022
DOI: 10.55529/jhtd23.19.30
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fat Replacers on the Multigrain Biscuits

Abstract: Nowadays, people are concerned about their health due to the change and modification in lifestyle. People demand a ready to eat food products that are healthy and safe. Biscuits or cookies are the most consumed snack product that gives feeling of fullness for the hunger between two meals and also liked by the every age group people. But the bakery fats and shortenings that are used in the preparation of biscuits, contain trans fatty acids that are not good for health. In this study, biscuits were formulated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Sengar et al . (2022) used multigrain flour (corn flour, barley flour and refined wheat flour) and fat replacers such as polydextrose and whey protein concentrate (10%–50%) in biscuits and reported that the biscuit containing 40% fat replacer was optimum. Vurro et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sengar et al . (2022) used multigrain flour (corn flour, barley flour and refined wheat flour) and fat replacers such as polydextrose and whey protein concentrate (10%–50%) in biscuits and reported that the biscuit containing 40% fat replacer was optimum. Vurro et al .…”
Section: Introductionmentioning
confidence: 99%
“…Yashini et al (2021) used partially defatted tomato seed flour to replace of fat and reported that the fat replacer caused a significant decrease in fat and spread ratio of millet based cookies. Sengar et al (2022) used multigrain flour (corn flour, barley flour and refined wheat flour) and fat replacers such as polydextrose and whey protein concentrate (10%-50%) in biscuits and reported that the biscuit containing 40% fat replacer was optimum. Vurro et al (2022) investigated the effect of durum wheat oil used for replacing of sunflower oil on physicochemical feature of biscuit and reported that high amount of antioxidants extended the oxidation resistance of biscuits.…”
Section: Introductionmentioning
confidence: 99%